Blasting and Comminution Choices for the Management of the Mining Business - Dennis Cremonese; Jacopo Seccatore; Alexandre Passos; Tatiane Marin; Giorgio De Tomi (International Society of Explosives Engineers, 2016)
"In the mining industry, rock excavation is the first phase of the comminution process. Downstreamoperations such as secondary breaking, crushing and milling terminate the process, reducing the size of the grains down to the desired particle distribution. In such a cascade process, every process upstream heavily influences all the downstream operations. When rock excavation is carried out by drilling and blasting, a very economic source of energy (the explosive) is used at the utmost upstream; a more expensive source of energy (electricity) is employed for all the downstream phases. This means that managing the correct employ of the explosive energy is a form of managing the whole process, controlling the operational costs and therefore the profitability of the whole business. We simulated this cascade behavior, using as a starting point the experimental data obtained from small-scale block blasting, evaluating the influence of blasting on the grindability of the blasted material. This study showed the reduction in visible (particle size) and invisible fracturing (micro-cracking, resulting in a reduction of the Work Index WI). The particle size distribution for full-scale blasts was estimated by means of algorithm simulation, then we simulated the behavior of the comminution plant fed with the material possessing the characteristics previously estimated. All the costs (drilling, blasting, electric energy for the engines of the crushers and mill) were calculated and charted. The results show a clear curve that allows to estimate the minimum operating expenditure (OPEX) for the whole mine+plant framework. Being the WI dependent on the output on the blast, one can manage the performance and the expenditure of the whole comminution process by adjusting drilling and blasting parameters For any given mine, it is possible to perform a simulation and encounter the minimum OPEX scenario for the comminution process and managerial choices can be oriented accordingly. In a cascade productive chain as mining is, responsible strategic choices must be taken looking at the entire production framework. Compartmentalized managerial staff and budgets for separated production areas are not acceptable anymore. Somehow higher costs upstream can lead to effective decrease in costs and increase in efficiency and productivity of the processes downstream."